The Influence of Teachers’ Code Switching on Students’ Understanding of Their Messages - Haryanti, Ari Putri; Mujiyanto, Januarius; Faridi, Abdurrachman (English Education Journal, 2018)
In Indonesia, English is a compulsory subject that is learnt by students for the first time in junior high school. Although the teachers are expected to use English in the classroom, sometimes students do not understand the explanation. Code switching becomes a natural part of classroom interaction in foreign language classroom. Therefore, this study aimed to explain the use of code switching, students perceived the teachers’ code switching, the students respond to the teacher’s code-switching practices and the influence of teachers’ code-switching practices on students’ understanding in the teaching learning process. It was conducted at SMP N 1 Comal. The method used in this research was qualitative study. To get the data, researcher used observation, video recording, questionnaire and interview. The results of the study showed that first there were six functions of code switching in the foreign language classroom, those are to explain grammar, to manage classroom, to index a stance of empathy or solidarity, to translate words, to help students when they have difficulty in understanding and to emphasis some points. Second, the students preferred a combination of Indonesia and English in the classroom. Third, there were five responses from students in the teaching learning process, those were specific response, choral response, open-ended or students initiated response, silence and laughter. Fourth, teachers believed that code switching had positive influences in teaching English for their students.